Innovative Acid-Base Learning Based On Augmented Reality: A Literature Review on Its Effectiveness in Enhancing Student Learning Outcomes - Yuhelman, Nofri; Rivaldo , Ifan; Burhan, Kristian; Sazaliana, Ade (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The integration of Augmented Reality (AR) into chemistry learning, particularly in acid-base topics, has emerged as a promising innovation to enhance student engagement and understanding. This literature review aims to analyze the effectiveness of AR-based learning in improving student learning outcomes on acid-base material. The study employs a systematic review method by collecting, screening, and analyzing articles published between 2018–2024 from indexed databases such as Scopus, Springer, and Google Scholar. A total of 25 relevant articles were identified and analyzed thematically to assess the impact of AR on cognitive achievement, conceptual understanding, and student motivation. The findings reveal that AR technology not only improves students' conceptual mastery but also reduces misconceptions and supports interactive, immersive learning experiences. Furthermore, AR enhances the visualization of microscopic and abstract acid-base phenomena, which are typically difficult for students to comprehend through conventional instruction. The review concludes that AR is a pedagogical innovation with significant potential to transform acid-base chemistry instruction. Further empirical studies are recommended to explore long-term impacts and classroom integration strategies.